Secrets of the circus revealed - Ellingsen, Ray; Martin, Jean-Lue; Van Loo Productions (Australia : Van Loo Productions, 2002)
This program offers the rare opportunity t develop a variety of skills from some of the circus's outstanding artists. Increase fitness level, strength and coordination while learning these impressive skills
Title from title screen
Volume 1 - volume 4
Executive producer, Christine Van Loo ; camera operators, Mishael Johnson, Rex Blatter
Hosted by Richard Hatch with Jean-Lue Martin, Christine Van Loo
DVD format
Keywords: Acrobatics; Circus